Staying Alive: Leadership in COVID-19 World - Stewart, Carol (Journal of Leadership, Accountability & Ethics, 2021)
While this unprecedented time of COVID-19 has resulted in financial loss for many companies, it's also produced new leadership opportunities. Remote work, at-home schooling, and socially-distancing are a few examples of the new norm and new business possibilities. As crisis proverbially breeds innovation, new businesses have already sprung up around the world in support of growing demands. History shows this growth in entrepreneurial endeavors to be a trend during times of economic downturn. More than half of 2009 Fortune 500 list and just under half of 2008's Inc. list were created during a recession or bear market. Challenging economic times often seed the growth of entrepreneurial capitalism. One reason for this growth is that startup companies begun during times of high stress tend to be capable of operating in less favorable conditions. In times of economic upheaval, even mature businesses with longer history and deeper pockets require special leadership to 'pivot' their operational strategies to stay viable. This paper explores effective leadership theories to explain the success during uncertain times.
Keywords: BEAR markets; COVID-19; LEADERSHIP; NEW business enterprises; SITUATIONAL leadership theory; TELECOMMUTING; dept.mgt; entrepreneurship; leadership; pandemic; peer-reviewed; pivoting; situational leadership